Health-related quality of life in teenagers with a parent with cancer. (June 2016) - Jeppesen, Elisabeth; Bjelland, Ingvar; Fosså, Sophie D.; Loge, Jon H.; Dahl, Alv A.
Abstract: Purpose: Health-related quality of life (HRQoL) in teenagers exposed to parental cancer has shown divergent results as an outcome measure. In this study we wanted to: 1) compare the HRQoL of teenagers exposed to parental cancer (CASES) with normative European HRQoL data (NORMs) measured close to parental diagnosis and treatment; 2) study changes in the HRQoL of CASES from baseline to follow-up; 3) explore sex differences in the HRQoL of CASES; and 4) explore eventual confounders of HRQoL of CASES at baseline. Methods: Forty-five families with one parent diagnosed with primary invasive cancer were included, these families had 69 teenagers. At the follow-up, 26 families with 29 teenagers complied. Both parents and teenagers filled in electronic questionnaires over the Internet. HRQoL in teenagers was self-rated by the KIDSCREEN-27 at baseline and follow-up, and the responses were compared to a European normative sample (NORMs). Results: 1) The teenagers scored significantly lower on the Physical well-being dimension compared to the NORMs at baseline, while no significant differences were observed concerning the four other HRQoL dimensions. 2) Some significant improvements were observed on HRQoL dimensions from baseline to follow-up. 3) CASES girls showed a trend towards lower HRQoL scores compared to boys. 4) Parental cancer-related characteristics and family function were not related to teenagers' HRQoL, but so were teenagers' self-esteem. Conclusions: At group level, living with a parent who receives curative treatment for a recently diagnosed cancer affects teenagers' HRQoL to certain extent. Self-esteem is a confounder to teenagers' HRQoL in our sample. Highlights: Health Related Quality of life (HRQoL) has hardly been studied before in teenagers exposed to parental cancer. To our knowledge, this study is one of few investigating the impact of parental cancer on teenagers' HRQoL using an internationally instrument with good psychometric properties, the KIDSCREEN-27. Aims 1) to compare the HRQoL of teenagers exposed to parental cancer, diagnosed within the preceding year, with normative European HRQoL data for teenagers; 2) to study changes in the HRQoL from baseline to follow-up six to eight months later. HRQoL in teenagers with parents with cancer did not differ significantly from norm data except for Physical well-being that was poorer among Case. The HRQoL dimensions scores were stable over time. The KIDSCREEN questionnaire seems to be a valid measure of HRQoL in teenagers exposed to parental cancer. Using an electronic questionnaire has been a successful tool.